Export Performance of Textile and Apparel Products: A Comparative Study of Bangladesh and Malaysia - Haque, A. K. M. Ahasanul (2001)
The textile and apparel industry provides the major source of foreign exchange earnings of Bangladesh and Malaysia. Impressive export growth and upward performance continuously turn the industry into a viable contributor to the national economy. The objectives of the study are: firstly, to examine the export competitiveness of textile and apparel products of Bangladesh and Malaysia, using economic indicators like Revealed Comparative Advantage (RCA) and Constant Market Share (CMS) analysis. Secondly, to examine the potential export markets using Shift-Share technique. The RCA calculations clearly show an increasing strength of comparative advantage to Bangladesh for the export of textile as well as apparel products. This is mainly due to the negligible import for textile and apparel products. In the case of Malaysia, the RCA calculations also show an increasing strength of comparative advantage of export performance ratio for the export of textile and apparel products. The net export/total trade ratio shows an increasing strength of RCA only for the apparel products, but for the export of textile products, the RCA is shown negative ratio. This is mainly due to the excessive import of textile products. The CMS results suggest that export gains of both countries for textile and apparel products are largely attributed to the size of the market effect and also to their competitiveness effect. Regarding the export growth of selected textile products for both countries, the CMS results demonstrate that, in most cases, Malaysia shows better competitive performance than that of Bangladesh. For commodity composition and market distribution effects, Malaysia shows better performance in most of the cases and has attained advantage in world trade for overall textile articles compared to Bangladesh. In the case of apparel products, both countries show negative export performance of commodity composition and market distribution effects. CMS analysis depicts that the competitiveness effects of both countries for these apparel products subsequently improved in general during the period 1 992- 1 996 as compared to those for periods of 1 982-86 and 1 987-9 1 . During the period of the study, Bangladesh registered on average better performance with regards to commodity composition and market distribution effects for apparel products as compared to Malaysia. The results of shift share analysis indicate that market opportunities for the export of textile and apparel products of Bangladesh are mainly offered by the USA, Canada and EU countries. However, Asian countries have shown a negligible role in this respect. On the other hand, USA, Canada and EU countries have also been identified as potential markets for Malaysia for textile and apparel products. In addition, the Asian region also offered better market opportunities to Malaysia.